Queenie : a Novel - Carty-Williams, Candice 1989- (New York : Scout Press, 2019)
"Queenie Jenkins is a 25-year-old Jamaican British woman living in London, straddling two cultures and slotting neatly into neither. She works at a national newspaper, where she's constantly forced to compare herself to her white middle class peers. After a messy break up from her long-term white boyfriend, Queenie seeks comfort in all the wrong places--including several hazardous men who do a good job of occupying brain space and a bad job of affirming self-worth"--
Keywords: Women -- Fiction -- Identity; Self-realization in women -- Fiction; Multiculturalism -- Fiction; Jamaicans -- Fiction -- England; FICTION / Contemporary Women; FICTION / Literary; Psychological fiction